Fenomena Akiya di Jepang: Faktor Penyebab, Dampak, dan Solusi - Juhartono, Anissa Nabiilacahyani; Mulya, Komara (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2024)
This paper is motivated by the increasing number of akiya in Japan and the possibility of more abandoned akiya. This paper discussed the phenomenon of akiya that is happening in Japan. The data collection conducted for this paper uses the literature study method by collecting data from articles, journals, and websites. This paper is written to find out the factors causing the occurrence of akiya, the impact of the emergence of akiya, and the solutions carried out in solving akiya in Japan. Based on the results found, the causes of akiya are Japan's changing demographics, inheritance issues, urbanization, and the rise of new housing popularity. From these causes, there are environmental and legal impacts. There are local government efforts such as akiya banks, providing subsidies, informing and raising awareness of akiya management, and launching akari programs. There are also efforts from non-profit organizations. Efforts from the community are buying akiya, turning the akiya into a cafe, managing the akiya themselves, and establishing good relations with the neighborhood community.